AKTIVITAS ANTIOKSIDAN FUNGI ENDOFIT HERBA KROKOT (Portulaca oleracea L.) - Siska Nuryanti; Asriani Suhaenah; Rachmat Faisal Syamsu; Rini Andriani (As-Syifaa Jurnal Farmasi, 2023)
Purslane herb (Portulaca oleracea L.) is one of the plants that is considered as a valuable plant in the pharmaceutical world for the future because of its antioxidant content and high nutritional value. Endophytic fungi can produce secondary metabolites that have activities similar to those produced by their host plants, where these metabolites have medicinal potential. In previous studies, it was found that the ethyl acetate extract of endophytic fungi had antidiabetic activity in the α-glucosidase enzyme inhibition test. This research aims todetermine the antioxidant activity of the ethyl acetate extract of the endophytic fungus of purslane herb (Portulaca oleracea L.) using the Test method1,1-diphenyl-2-picrylhydrazyl(DPPH). Purslane herbaceous endophytic fungus isolate (Portulaca oleracea L.) code FEK purified for 3 days. Then, fermented using MYB medium for 21 days. After that, extracted to become a thick extract. Furthermore, the DPPH test was carried out using a vitamin C comparison solution. Based on the IC50 value of the ethyl acetate extract of the endophytic fungus of purslane herb code FEK, it was found to be 64.26 μg/mL which is a relatively strong antioxidant activity